Value Co-Creation In E-Commerce Platforms: The Role Of Personality Traits And Trust - Widyastuti Widyastuti (Folia Oeconomica Stetinensia)
It is important for companies to pay attention to the value of co-creation in order to encourage innovation and the development of new products where the source of ideas for innovation and new products comes from consumers. Participation in value co-creation is voluntary and depends on the consumer’s willingness to be involved, so there needs to be motivation within the consumer to carry out value co-creation. Therefore, it is necessary to understand the consumer’s personality which can encourage co-creation.